TAG SWITCHING FOUND IN INSTAGRAM: A SOCIOLINGUISTIC APROACH - Yunita, Rika Rahma; Suryani, Melly Siska (LPPM Universitas Putera Batam, 2019)
This research is a sociolinguistic research that investigates the relationship between language and society, especially in the use of tag switching. The purpose of this research is to find out the type of tag switching that is used by instagram users in the #jakselliterary and to know the function of tag switching that is done by the instagram users. This research is a qualitative descriptive study. The object of the research is tag switching in the #anakjakselliterary instagram. In collecting data, researchers used the observation method and used the pragmatic identity method. To analyze the type of tag switching, researchers used the theory of Holmes (2001) and Poplack (1980). As well as to examine the function of tag switching, researchers used the theory by Appel and Muysken (1987). The results showed that the switching tags used in the #jakselliterary they are sentence fillers, interjection and discourse markers. In addition, researchers also found the function of tag switching, namely metalinguistic, directive, expressive, phatic, and poetic.